Chronic Stress protection for postnatal dEpREssioN prEvention (SERENE): a protocol for an exploratory study. Issue 5 (3rd May 2018) - Tharwat, Dahlia; Trousselard, Marion; Balès, Mélanie; Sutter-Dallay, Anne-Laure; Fromage, Dominique; Spitz, Elisabeth; Dallay, Dominique; Harvey, Thierry; Welter, Eric; Coatleven, Frédéric; Cherier, Lydie; Teissèdre, Frédérique; et al.
Abstract : Introduction: The prevalence of postnatal depression (PND) is significant: reaching up to 20% in the general population. In mechanistic terms, the risk of PND lies in an interaction between a maternal psychophysiological vulnerability and a chronic environmental context of stress. On the one hand, repetition of stressor during pregnancy mimics a chronic stress model that is relevant to the study of the allostatic load and the adaptive mechanisms. On the other hand, vulnerability factors reflect a psychological profile mirroring mindfulness functioning (psychological quality that involves bringing one's complete and non-judgemental attention to the present experience on a moment-to-moment basis). This psychological resource is linked to protective and resilient psychic functioning. Thus, PND appears to be a relevant model for studying the mechanisms of chronic stress and vulnerability to psychopathologies. In this article, we present the protocol of an ongoing study (started in May 2017). Methods and analysis: The study is being carried out in five maternities and will involve 260 women. We aim to determine the predictive psychobiological factors for PND emergence and to provide a better insight into the mechanisms involved in chronic stress during pregnancy. We use a multidisciplinary approach that encompasses psychological resources and biophysiological and genetic profiles in order to detect relevant vulnerability biomarkers for chronic stress and the development of PND. To do so, each woman will be involved in the study from her first trimester of pregnancy until 12 months postdelivery. Ethics and dissemination: Ethics approval was obtained from the Ile de France III Ethics Committee, France (2016-A00887-44). We aim to disseminate the findings through international conferences and international peer-reviewed journals. Trial registration number: NCT03088319 ; Pre-results.